An Intelligent DNA Nanorobot for Autonomous Anticoagulation. (11th August 2020) - Yang, Linlin; Zhao, Yumeng; Xu, Xuemei; Xu, Kangli; Zhang, Mingzhi; Huang, Kui; Kang, Huaizhi; Lin, Hsiao‐chu; Yang, Yang; Han, Da
Abstract: Artificial nanorobots that can recognize molecular triggers and respond with programable operations provide an inspiring proof‐of‐principle for personalized theragnostic applications. We have constructed an intelligent DNA nanorobot for autonomous blood anticoagulation in human plasma. The DNA nanorobot comprises a barrel‐shaped DNA nanostructure as the framework and molecular reaction cascades embedded as the computing core. This nanorobot can intelligently sense the concentration of thrombin in the local environment and trigger an autonomous anticoagulation when excess thrombin is present. The triggering concentration of thrombin at which the nanorobot responds can be tuned arbitrarily to avoid possible side effects induced by excess thrombin. This makes the nanorobot useful for autonomous anticoagulation in various medical scenarios and inspires a more efficient and safer strategy for future personalized medicine. Abstract : A DNA nanorobot is presented that can intelligently regulate thrombin functions when it senses an over‐boosted coagulation environment. Under normal coagulation conditions it does not perform. The trigger concentrations of nanorobot can be tuned arbitrarily, which makes the nanorobot useful for autonomous anticoagulation in various medical scenarios and inspires a more efficient and safer strategy for personalized medicine.